IDENTITY POLITICS AND ELECTORAL CHALLENGES OF THE INDONESIAN DEMOCRATIC PARTY OF STRUGGLE (PDIP) IN WEST SUMATERA - Nafil Fadlul Rahman; Nunik Retno Herawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Research on the Indonesian Democratic Party of Struggle (PDIP) has so far been dominated by the focus of studies in the Java region, especially related to its support base and electoral dynamics. Meanwhile, studies on PDIP in the Sumatra region, especially West Sumatra, are still relatively limited. In fact, the different socio-political contexts in this region have their own dynamics, especially in relation to identity politics and electoral challenges faced by PDIP. This research will examine the dynamics of identity politics and electoral challenges faced by the Indonesian Democratic Party of Struggle (PDIP) in West Sumatra. As a nationalist party that has an ideology that is often considered contrary to the cultural and religious sentiments of the Minangkabau people, PDIP has had difficulty gaining significant support in this area. Through a cultural-political approach, this study analyzes how people's collective identities, historical narratives, and the formation of customary and religious values affect political preferences that tend to be conservative and resistive to PDIP. This study uses a qualitative method with a literature study approach and discourse analysis to investigate the construction of identity politics behind PDIP's low electability. The results of this study show that rejection of PDIP in West Sumatra is not only caused by policy or performance issues, but also influenced by ideological perceptions, historical trauma, and the strengthening of local identity that is contrary to PDIP's image of nationalism. These findings underscore the importance of contextual political communication strategies that are sensitive to local cultural dynamics in the face of electoral contestation.